Biofilms, active substrata, and me. (1st April 2018) - Rittmann, Bruce E.
Abstract: Having worked with biofilms since the 1970s, I know that they are ubiquitous in nature, of great value in water technology, and scientifically fascinating. Biofilms are naturally able to remove BOD, transform N, generate methane, and biodegrade micropollutants. What I also discovered is that biofilms can do a lot more for us in terms of providing environmental services if we give them a bit of help. Here, I explore how we can use active substrata to enable our biofilm partners to provide particularly challenging environmental services. In particular, I delve into three examples in which an active substratum makes it possible for a biofilm to accomplish a task that otherwise seems impossible. The first example is the delivery of hydrogen gas (H2 ) as an electron donor to drive the reduction and detoxification of the rising number of oxidized contaminant: e.g., perchlorate, selenate, chromate, chlorinated solvents, and more. The active substratum is a gas-transfer membrane that delivers H2 directly to the biofilm in a membrane biofilm reactor (MBfR), which makes it possible to deliver a low-solubility gaseous substrate with 100% efficiency. The second example is the biofilm anode of a microbial electrochemical cell (MxC). Here, the anode is the electron acceptor for anode-respiring bacteria, which "liberate" electrons from organic compounds and send them ultimately to a cathode, where we can harvest valuable products or services. The anode's potential is a sensitive tool for managing the microbial ecology and reaction kinetics of the biofilm anode. The third example is intimately coupled photobiocatalysis (ICPB), in which we use photocatalysis to enable the biodegradation of intrinsically recalcitrant organic pollutants. Photocatalysis transforms the recalcitrant organics just enough so that the products are rapidly biodegradable substrates for bacteria in a nearby biofilm. The macroporous substratum, which houses the photocatalyst on its exterior, actively provides donor substrate and protects the biofilm from UV light and free radicals in its interior. These three well-developed topics illustrate how and why an active substratum expands the scope of what biofilms can do to enhance water sustainability. Graphical abstract: Image Highlights: Biofilms are ubiquitous in Nature and widely useful in environmental biotechnologies. Active substrata can allow biofilms to achieve important, but very difficult tasks. Hydrogen gas can be delivered as an electron donor to reduce oxidized contaminants. The anode of a microbial electrochemical cell can be the electron acceptor. A macroporous carrier can allow intimate coupling of photocatalysis and biodegradation of recalcitrant organics.